Jamu Industry Products Development and Their Instutional Structure Analysis - Kusnandar .; Marimin . (Jurnal Teknologi dan Industri Pangan, 2003)
Indonesia is a rich country for many kinds of medicinal plants which become important raw material for jamu industry development. This paper discusses jamu industry products selection and institutional structure analysis for the jamu industry development. The result of products selection using Ã¢â‚¬Å“fuzzy non numeric decision making techniqueÃ¢â‚¬Â shows that powder jamu is the best product to be developed and institutional structure analysis using Ã¢â‚¬Å“interpretative structural modelling techniqueÃ¢â‚¬Â shows that municipal goverment is the institution which has strongest driver power for jamu industry development. Key words : Interpretative structural modelling, jamu industry, and decision making